(3GdEYdGe HGdCYdGe JGQjN HjJ Gddg GdMQGes - (3eMeO Hf CMeO Hf eMeO Hf bGVj NGf eMehO GdfgQhGdj GdMfaj Gdecj , bWH GdOjf,J (B988 (3g` s ((3eMeO (B((3cPG(B)q s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdeSLO GdMQGe MQeG BefG heKGHI ddfGS hCeQ HJWgjQ GdcYHI GdHjJ GdMQGe ddWGFajf hGdYGcajf hCRGd YfgG GdNha hGdHGS s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe GdCJeGf GdCcedGf Ydi SjO GdCfHjGA hGdeQSdjfq s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B17s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B126s
Keywords: (3GdJGQjNs